2021
DOI: 10.3390/ijerph18147418
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Photobiomodulation in the Treatment of Cancer Chemotherapy-Induced Oral Mucositis: A Meta-Analysis with Trial Sequential Analysis

Abstract: Oral mucositis is a debilitating complication of chemotherapy, characterized by erythema, ulcers and oedema of the oral mucosa. This review aimed to evaluate the efficacy of Photobiomodulation in the treatment of oral mucositis using meta-analysis and trial sequential analysis, and also to assess the quality of the results by Grading of Recommendations, Assessment, Development and Evaluation (GRADE). A comprehensive search of three databases, including Embase, Medline and Central, was performed to identify ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
6
0
1
Order By: Relevance
“…(35) The target area was covered with total ED of 5.4 J/cm 2 that was used based on the recommendations of similar trials using energy densities ranging from 2 to 8 J/cm 2 . (35,36) Results of the current study revealed clinically that there was no statistically significant difference among the four groups up to day 7, that revealed the highest MD score, which was in agreement with similar studies. (37) The mean MD score did not exceed 3 in the three therapeutic groups, in contrast to CG with the mean MD score reaching 3.5 on days 8 and 9, reflecting the positive role of the therapeutic agents in managing the condition.…”
Section: Discussionsupporting
confidence: 91%
“…(35) The target area was covered with total ED of 5.4 J/cm 2 that was used based on the recommendations of similar trials using energy densities ranging from 2 to 8 J/cm 2 . (35,36) Results of the current study revealed clinically that there was no statistically significant difference among the four groups up to day 7, that revealed the highest MD score, which was in agreement with similar studies. (37) The mean MD score did not exceed 3 in the three therapeutic groups, in contrast to CG with the mean MD score reaching 3.5 on days 8 and 9, reflecting the positive role of the therapeutic agents in managing the condition.…”
Section: Discussionsupporting
confidence: 91%
“…With a strong base of evidence, the MASCC/ISOO guidelines advise using PBM to avoid oral mucositis brought on by chemotherapy and radiotherapy. http://dx.doi.org/10.52533/JOHS.2022.21210 A recent meta-analysis published after the latest update of MASCC/ISOO included recently emerging evidence to support the efficacy of photobiomodulation in the management of cancer chemotherapy-induced oral mucositis (50). Their findings illustrated that photobiomodulation is an effective therapeutic intervention for reducing oral mucositis severity, so it is advised for the treatment (50).…”
Section: Laser Therapymentioning
confidence: 99%
“…http://dx.doi.org/10.52533/JOHS.2022.21210 A recent meta-analysis published after the latest update of MASCC/ISOO included recently emerging evidence to support the efficacy of photobiomodulation in the management of cancer chemotherapy-induced oral mucositis (50). Their findings illustrated that photobiomodulation is an effective therapeutic intervention for reducing oral mucositis severity, so it is advised for the treatment (50). The use of extra-and intra-oral lasers on patients receiving RT for head and neck cancer resulted in improved clinical outcomes and a decrease in oral mucositis (51).…”
Section: Laser Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Oral mucositis (OM) is an inflammatory condition of the oral mucosa characterized by painful erythematous and ulcerative lesions in the oral cavity [ 1 ]. OM occurs as a common side effect in patients with cancer receiving chemotherapy (CTx) and radiotherapy (RT), which can be severe and impede the quality of life [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%